'Back to the "futur"': Mobility and immobility through English in Algeria. (September 2019) - Jacob, Camille
Abstract: Based on year-long ethnographic fieldwork, this paper examines how global discourses of English as the "international language" are read, reproduced and appropriated in non-Anglophone postcolonial settings, taking Algeria as a case study. English is heralded as the "language of the future", equated with "moving on" from the colonial past towards new connections, new horizons, and new articulations of a global-national identity. It is both a movement forward, and an attempt at reaching back to a more "authentic" (non-Francophone) past. However, those narratives are also firmly embedded within existing power hierarchies and prevailing language ideologies. Discourses and practices around English reinforce rather than challenge socio-economic stratification by rewarding elite mobilities and reproducing representations of how language indexes authenticity and belonging. Highlights: Global discourses about English are appropriated to symbolise spatial, social and temporal mobility. They become tool and symbol of new categories articulating transnational belonging. They are used to re-imagine an authentic past leading to a more authentic future. They contribute to the reproduction rather than questioning of socioeconomic hierarchies.